2021
DOI: 10.3343/alm.2021.41.6.559
|View full text |Cite
|
Sign up to set email alerts
|

Disk Diffusion Susceptibility Testing for the Rapid Detection of Fluconazole Resistance in Candida Isolates

Abstract: Background: Given the increased fluconazole resistance (FR) among Candida isolates, we assessed the suitability of disk diffusion susceptibility testing (DDT) for the early detection of FR using well-characterized Candida isolates.Methods: In total, 188 Candida isolates, including 66 C. albicans (seven Erg11 mutants), 69 C. glabrata (33 Pdr1 mutants), 29 C. parapsilosis (15 Erg11 mutants), and 24 C. tropicalis (eight Erg11 mutants) isolates, were tested in this study. FR was assessed using DDT according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The results showed a very good agreement rate between both methods (97.1%). These findings are in conformity with those conducted by Jeon et al, 2021 43 and Kumar et al, 2015 44 . They reported 97%, 100% categorical agreement between DD method and the BMD method for assessing FLZ susceptibility against C. albicans isolates 43,44 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed a very good agreement rate between both methods (97.1%). These findings are in conformity with those conducted by Jeon et al, 2021 43 and Kumar et al, 2015 44 . They reported 97%, 100% categorical agreement between DD method and the BMD method for assessing FLZ susceptibility against C. albicans isolates 43,44 .…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in conformity with those conducted by Jeon et al, 2021 43 and Kumar et al, 2015 44 . They reported 97%, 100% categorical agreement between DD method and the BMD method for assessing FLZ susceptibility against C. albicans isolates 43,44 . Kumar et al concluded that DD methods can be used as substitute for the reference BMD method for Candida spp susceptibility testing of FLZ 44 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, similar to our findings, recent studies have demonstrated that the DD antifungal susceptibility method showed a good agreement with the BMD method for Candida spp., including C. glabrata and C. auris [22,23]. However, the use of a larger inoculum may detect fluconazole-resistant Candida species more rapidly and reliably [24].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the antifungal effect of six synthesized ionic liquids, the disc diffusion method was used based on standard CLSI M44-A2 ( Method for Antifungal Disk Diffusion Susceptibility Testing of Yeasts) ( 16 ). After evaluating the ILs antifungal ability, the powerful IL against candida growth was selected for continued experimental.…”
Section: Methodsmentioning
confidence: 99%